Can bottom-up synthetic biology generate advanced drug-delivery systems? - Lussier, Félix; Staufer, Oskar; Platzman, Ilia; Spatz, Joachim P. (Trends in biotechnology, 2021)
Creating a magic bullet that can selectively kill cancer cells while sparing nearby healthy cells remains one of the most ambitious objectives in pharmacology. Nanomedicine, which relies on the use of nanotechnologies to fight disease, was envisaged to fulfill this coveted goal. Despite substantial progress, the structural complexity of therapeutic vehicles impedes their broad clinical application. Novel modular manufacturing approaches for engineering programmable drug carriers may be able to overcome some fundamental limitations of nanomedicine. We discuss how bottom-up synthetic biology principles, empowered by microfluidics, can palliate current drug carrier assembly limitations, and we demonstrate how such a magic bullet could be engineered from the bottom up to ultimately improve clinical outcomes for patients.
Online 7 September 2020
Gesehen am 09.06.2021